Factors associated to stigma in mental health workers of Castilla y Leon. The role of burnout and work motivation - J.M. Pelayo-Terán; Y. Zapico-Merayo; M.E. Garcia Llamas; S. Vega-García; C. López-Zapico; M.R. Villa-Carcedo; Á. Álvaro-Prieto (European Psychiatry, 2022)
Introduction Stigma is one of the most important barriers to help-seeking, treating maintenance and recovery for people suffering mental disorders. These attitudes, when present in mental health workers, may have a negative effect on the quality of health care.